2019
DOI: 10.3390/polym11101559
|View full text |Cite
|
Sign up to set email alerts
|

HDPE/Chitosan Composites Modified with PE-g-MA. Thermal, Morphological and Antibacterial Analysis

Abstract: In this work, composites of high density polyethylene (HDPE) with chitosan were prepared by melt compounding in a laboratory internal mixer. Maleic anhydride grafted HDPE (PE-g-MA) in a concentration up to 25 phr was used as a compatibilizer to enhance the dispersing effect of chitosan in the HDPE matrix. The degree of crystallinity was investigated by X-ray diffraction (XRD) and the thermal properties were analyzed by differential scanning calorimetry (DSC) and thermogravimetry (TG). The morphology was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…The reduction in glass particle aggregation is due to an interaction between the surface hydroxyl groups of glass and the carbonyl groups of MAgPE attached to the polymeric matrix, which enhances the mechanical properties of the composites [ 24 , 27 , 28 ]. In comparison with the different concentrations of the reinforced waste glass powder, the size of aggregation increased with increasing glass phase content in the polymeric matrix phase, which agrees with previous studies [ 29 , 30 , 31 ].
Figure 6 SEM images of (a) raw RHDPE, (b) raw WGP, RHDPE/WGP composites without compatibilizer (c) 5 wt%, (e) 10 wt%, (g) 20 wt% and (i) 30 wt% WGP content and RHDPE/MAgPE/WGP composites with 1.5 wt.% MAgPE as a compatibilizer where (d) 5 wt%, (f) 10 wt%, (h) 20 wt% and (j) 30 wt% WGP content.
…”
Section: Resultssupporting
confidence: 91%
“…The reduction in glass particle aggregation is due to an interaction between the surface hydroxyl groups of glass and the carbonyl groups of MAgPE attached to the polymeric matrix, which enhances the mechanical properties of the composites [ 24 , 27 , 28 ]. In comparison with the different concentrations of the reinforced waste glass powder, the size of aggregation increased with increasing glass phase content in the polymeric matrix phase, which agrees with previous studies [ 29 , 30 , 31 ].
Figure 6 SEM images of (a) raw RHDPE, (b) raw WGP, RHDPE/WGP composites without compatibilizer (c) 5 wt%, (e) 10 wt%, (g) 20 wt% and (i) 30 wt% WGP content and RHDPE/MAgPE/WGP composites with 1.5 wt.% MAgPE as a compatibilizer where (d) 5 wt%, (f) 10 wt%, (h) 20 wt% and (j) 30 wt% WGP content.
…”
Section: Resultssupporting
confidence: 91%
“…In this case, the improvement in ductility due to PE- g -MA addition can be proved by FESEM observation. These results are closely related to the results reported by Lima et al [ 62 ], where PE- g -MA provided an improvement in ductility and plasticization of a biobased high density polyethylene and its compounds.…”
Section: Resultssupporting
confidence: 91%
“…Despite there not being a direct change in tensile properties, the presence of PE- g -MA seems to enhance some plasticization of BioHDPE, which can be observed in the morphology section (see Figure 3 ), where a higher plastic deformation can be assessed from FESEM observation. Lima et al [ 62 ] showed how the incorporation of 5% and 10% of PE- g -MA into a HDPE matrix did not change the maximum strength and Young’s modulus, while an increase in the elongation at break was observed. In addition to this, the most important role of PE- g -MA in BioHDPE-natural fiber composites is compatibilization due to its dual functionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite effect was only noted for the PE-g-MA compatibilizer, which is due to the high content of maleic anhydride, which may increase the spherulite size. Similar effects were noted in the work of Lima et al [ 97 ]. Such an effect can also be seen when comparing samples containing SEBS and SEBS-g-MA.…”
Section: Resultssupporting
confidence: 90%